English Part-Time Teachers’ Burnout Experiences in Indonesia Education Context - Elza Fauziah Harahap; Sholihatul Hamidah Daulay; Farida Repelita Waty Kembaren (Vifada Journal of Education, 2026)
Teachers constantly face demands beyond their control in their daily lives as educators, due to their profession being considered noble because it influences the character formation of many people, making it a burden for them. If this condition is left unaddressed, it will disrupt the teaching and learning process in the classroom and also cause burnout. This research aims to capture how English part-time teachers at junior high schools in Medan interpret the burnout they experience. A qualitative design with an interpretative phenomenological approach was used as a guideline for conducting the research efficiently. The research subjects include 6 part-time teachers who have been selected according to the research participant criteria. Data were collected through observation and in-depth interviews. The research findings revealed the main themes: the experiences of English part-time teachers regarding their burnout. The finding analyzes how teachers perceive the burnout they experience while teaching, which is accompanied by social interactions between teachers and students during the teaching and learning process in the classroom. Therefore, this research aims to alleviate the conditions of English part-time teachers in junior high schools in Medan by guiding them to understand their emotional states and how to cope with them.